2020
DOI: 10.3390/app11010072
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Three-Dimensional and Vortical Flow Phenomena to Enhance the Power Performance of a Wind Turbine Blade

Abstract: The performance of a wind turbine generator (WTG) is highly dependent on the interaction of a rotor blade with complex fluid behaviors, especially the induced vortex structure. In this paper, vortical flows around a blade were first investigated by the unsteady Reynolds averaged Navier–Stokes (RANS) simulation with shear stress transport (SST) turbulence model. It showed that the vortical flows were strongly formed at the blade tip due to the 3D behavior of the boundary layers dominated by pressure gradient. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…59 This form (although any other shape and arrangement is also possible) is most often employed on the root sections of large-scale wind turbine blades to mitigate the effects of flow separation. Given the importance of the topic, a truly great number of both experimental [60][61][62][63] and numerical [64][65][66][67][68][69][70][71] research studies is available. Different VGs are experimentally explored by Zhang et al 60 The results show that the maximum lift coefficient increases with VGs installed toward the leading edge of airfoils.…”
Section: Passive Flow Controlmentioning
confidence: 99%
“…59 This form (although any other shape and arrangement is also possible) is most often employed on the root sections of large-scale wind turbine blades to mitigate the effects of flow separation. Given the importance of the topic, a truly great number of both experimental [60][61][62][63] and numerical [64][65][66][67][68][69][70][71] research studies is available. Different VGs are experimentally explored by Zhang et al 60 The results show that the maximum lift coefficient increases with VGs installed toward the leading edge of airfoils.…”
Section: Passive Flow Controlmentioning
confidence: 99%
“…Huang et al [16] used a hybrid numerical simulation method to predict the typhoon wind field over complex terrain; they found that, after taking the effect of topography into account, the hybrid numerical simulation method can give a better prediction of the hourly mean wind speed and direction. To make full use of mountain environmental resources, in recent years, the efficient combination of geotechnical engineering design [17][18][19][20] and related mountain construction projects has further enhanced the complexity of the mountain environment where the transmission tower is located [21][22][23][24][25]. Based on the actual environmental conditions of undulating terrain, it is necessary to fully study the impact of external actual soil and mountains on the wind site of the transmission tower.…”
Section: Introductionmentioning
confidence: 99%